PENGARUH KERJASAMA TIM DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. ASTA JAWA DWIPA SURABAYA - Krisna Bahrul Ulum; Endang Iryanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This objectives examines the effect of teamwork and work motivation on employee performance at PT Asta Jawa Dwipa Surabaya, which has experienced a decline in performance in the last three years. Using a quantitative sociative approach with Partial Least Square (PLS) analysis on 72 permanent employees, the results of the study indicate that teamwork and work motivation have a significant effect on employee performance. The results of the analysis show that the path coefficients are 0.538 for teamwork and 0.416 for work motivation, with T-Statistic values ​​of 3.081 and 2.473, respectively, which are significant. This study reveals that good teamwork and high work motivation can increase employee productivity and work quality, as well as achieve company goals. Further efforts are needed to improve cooperation and motivation to maximize employee performance.